Modeling and simulating the effects of a general imperfect interface in fibrous piezoelectric composites. (December 2020) - Liu, J.-T.; Xu, Y.; He, Q.C.
Abstract: Interfacial behavior within fibrous piezoelectric composites (PZCs) may dramatically degrade the overall electromechanical performance and simultaneously vary the effective coupling moduli of these intelligent materials. In the present paper, we first recapitulate a physics-based general interfacial relation, which is rigorously derived from an ideal three-phase configuration and thus owns explicit physical meaning, to characterize this behavior between two different piezoelectric media. Afterwards, the explicit strong and weak governing equations of fibrous PZC boundary value problems (BVPs) are constructed, and a computational approach is then developed with the help of the extended finite element method (XFEM) to account for the discontinuities within both the primary (i.e., the electric potential and displacement fields) and the secondary fields (i.e., the normal electric displacement and normal traction fields). To achieve a benchmark problem with analytical exact solution, a simplified general interfacial relation is introduced, and a fibrous PZC BVP involving a cylindrical simplified general interface is designated and analytically solved. Hereafter, the convergence performance and validity of the elaborated computational approach are tested in detail. Eventually, discussions are further made on the influence of material composition and inhomogeneity shapes on the electroelastic coupling behavior of PZCs, and a few concluding remarks are drawn.